2020
DOI: 10.3390/electronics9020363
|View full text |Cite
|
Sign up to set email alerts
|

Demand and Storage Management in a Prosumer Nanogrid Based on Energy Forecasting

Abstract: Energy efficiency and consumers’ role in the energy system are among the strategic research topics in power systems these days. Smart grids (SG) and, specifically, microgrids, are key tools for these purposes. This paper presents a three-stage strategy for energy management in a prosumer nanogrid. Firstly, energy monitoring is performed and time-space compression is applied as a tool for forecasting energy resources and power quality (PQ) indices; secondly, demand is managed, taking advantage of smart applianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, more advanced control techniques have been reported that also engage controllable loads in combination with the generation and storage devices. Specifically, in [28] an energy management system (EMS) has been designed by considering the financial gain of the prosumer through three steps; namely energy monitoring, DSM through the available smart appliances, and management of the ESS in order to match the forecasted generation. The implementation of the proposed EMS results in improvement of the energy balance within the nanogrid.…”
Section: Adoption Of Nanogrids and Their Impactmentioning
confidence: 99%
“…However, more advanced control techniques have been reported that also engage controllable loads in combination with the generation and storage devices. Specifically, in [28] an energy management system (EMS) has been designed by considering the financial gain of the prosumer through three steps; namely energy monitoring, DSM through the available smart appliances, and management of the ESS in order to match the forecasted generation. The implementation of the proposed EMS results in improvement of the energy balance within the nanogrid.…”
Section: Adoption Of Nanogrids and Their Impactmentioning
confidence: 99%